Analisis Jual Beli Golok Dengan Cara Panjar menurut Perspektif Ekonomi Syariah di PG. Binangkit Cibeureum Tanjungsiang Subang - Abdul Abdul Hopid; Jalaludin jalaludin; Ahmad Damiri (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2021)
In Islam, muamalah is a form of convenience for humans to fulfill everything related to their daily needs as living beings and social beings, among the actions of the community to meet material needs is buying and selling with a down payment system, but some people still do not understand about the practice of buying and selling with a down payment system in a sharia economic perspective. This study aims to determine the sale and purchase of the down payment system according to the experts, and to find out the sharia economic review of buying and selling machetes in PG. Binangkit Cibeureum Tanjungsiang Subang. This research is a type of qualitative research with an empirical approach, the data collection techniques used are observation, interviews, and documentation. In this study, the data sources consist of primary data, namely PG managers and owners. Binangkit Kp. Cibeureum Tanjungsiang-Subang and secondary data in the form of records or archives in PG. Raise. Regarding jaul-buying using the Jurisprudence system, As-Syafi'i is of the opinion that it is invalid, based on the hadith narrated by Amru bin Shuaib which reads,